Study on neutrosophic graph with application in wireless network. Issue 4 (6th November 2020) - Fei, Yao
Abstract : A neutrosophic network is an extension of an intuitionistic fuzzy network that provides more precision compatibility and flexibility than an intuitionistic fuzzy graph in structuring and modelling many real‐life problems. The authors have explored the use of a neutrosophic network for modelling the passive optical network, mobile ad hoc network (MANET), and wireless sensor graph. They have presented the idea of strong arc, weak arc strong domination numbers, and strong perfect domination of neutrosophic network. They have described the method to find the values of strong and strong perfect domination of neutrosophic network. Finally, they use the idea of a strong arc strong domination number in MANET and wireless sensor graphs.